Critical dynamics of nonconserved N-vector models with anisotropic nonequilibrium perturbations - Dutta, Sreedhar B; Park, Su-Chan (Physical review. E, Statistical, nonlinear, and soft matter physics, 2011)
We study dynamic field theories for nonconserving N-vector models that are subject to spatial-anisotropic bias perturbations. We first investigate the conditions under which these field theories can have a single length scale. When N=2 or N≥4, it turns out that there are no such field theories and, hence, the corresponding models are pushed by the bias into the Ising class. We further construct nontrivial field theories for the N=3 case with certain bias perturbations and analyze the renormalization-group flow equations. We find that the three-component systems can exhibit rich critical behavior belonging to two different universality classes.